2021
DOI: 10.3390/w13060805
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Small-Scale Terrain on Precipitation

Abstract: Terrain plays an important role in the formation, development and distribution of local precipitation and is a major factor leading to locally abnormal weather in weather systems. Although small-scale topography has little influence on the spatial distribution of precipitation, it interferes with precipitation fitting. Due to the arbitrary combination of small, medium and large-scale terrain, complex terrain distribution is formed, and small-scale terrain cannot be clearly defined and removed. Based on the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The possible reason is limited precipitation in arid and semi-arid regions, which may be the main factor limiting vegetation growth [63]. It is also possible that the southwestern region is connected to the Loess Plateau region, and some studies have shown that topography significantly influences the spatial distribution of precipitation [64].…”
Section: Impact Of Climate Factors On Vegetation Changes 421 Precipit...mentioning
confidence: 99%
“…The possible reason is limited precipitation in arid and semi-arid regions, which may be the main factor limiting vegetation growth [63]. It is also possible that the southwestern region is connected to the Loess Plateau region, and some studies have shown that topography significantly influences the spatial distribution of precipitation [64].…”
Section: Impact Of Climate Factors On Vegetation Changes 421 Precipit...mentioning
confidence: 99%
“…Significantly more frequently, SWPp are observed in mountainous region of Crimea (224 cases in Aj-Petri) and SCC (106 cases in Yalta); however, precipitation is observed in the steppe region of the peninsula extremely rarely (only seven cases in Razdolnoe). One can put such a contrast in the number of cases of SWPs down to an influence of terrain relief on precipitation formation [25,26]. In particular, the precipitation depends on the height of the slopes, the horizontal dimensions of the uplands, the orientation, and the openness in relation to the moisture-carrying flow and general conditions of weathering.…”
Section: Swp Of Precipitation In Crimeamentioning
confidence: 99%
“…They also observed that heavy rainfall days exhibited a decrease before 2013, and the decreasing trend was alleviated after 2013. Given the spatiotemporal variability of mean and extreme precipitation climatology, several studies have analyzed the reasons for the observed differences [21][22][23][24][25], including geographical factors [26][27][28][29], global warming [30][31][32], circulation factors [11,[33][34][35][36], and urbanization [37,38].…”
Section: Introductionmentioning
confidence: 99%